RELEVANCE OF RUSKIN BOND’S STORIES IN THE CONTEMPORARY WORLD: A STUDY - Sharma, Paarull (International Journal of Psychosocial Rehabilitation, 2020)
Ruskin Bond has been hailed as the ‘Pioneer of English literature for children. Ruskin Bond has been contributing to the enrichment of English literature through his poems, essay, short stories and novels for nearly six decades. The author today has more than five hundred compilations to his credit. Despite its humble background and ordinary child characters of the hills Bond’s stories and characters have great relevance in today’s times as the world races towards materialistic and technological innovations? A world where new borns are exposed to the gadgets long before they know what it is. The little ones are experts at handling mobiles and impeccably play on the video games but lack completely in moral conduct and social skills. Ruskin Bond’s stories and characters act as a moral guide to these urban locales especially the adolescents.